2018
DOI: 10.1063/1.5028557
|View full text |Cite|
|
Sign up to set email alerts
|

Free energy of adhesion of lipid bilayers on silica surfaces

Abstract: The free energy of adhesion per unit area (hereafter referred to as the adhesion strength) of lipid arrays on surfaces is a key parameter that determines the nature of the interaction between materials and biological systems. Here we report classical molecular simulations of water and 1,2-dimyristoylsn-glycero-3-phosphocholine (DMPC) lipid bilayers at model silica surfaces with a range of silanol densities and structures. We employ a novel technique that enables us to estimate the adhesion strength of supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Note that the critical diameter changes depending on the nature of the nanoparticle surface. Molecular simulations 30,31 have shown that for neutral crystalline silica surfaces the critical diameter as defined above, obtained from predictions of W; is~16 nm while for amorphous silica is~10 nm. For AuNPs the critical diameter is much smaller (~4 nm) based on the experimental data/simulation prediction of W = 42 mN m −1 32 for a bare gold surface.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Note that the critical diameter changes depending on the nature of the nanoparticle surface. Molecular simulations 30,31 have shown that for neutral crystalline silica surfaces the critical diameter as defined above, obtained from predictions of W; is~16 nm while for amorphous silica is~10 nm. For AuNPs the critical diameter is much smaller (~4 nm) based on the experimental data/simulation prediction of W = 42 mN m −1 32 for a bare gold surface.…”
Section: Resultsmentioning
confidence: 94%
“…where Àk w is the simulated absorption strength on a flat surface [30][31][32]34 , a is the wrapping diameter equal to the nominal radius plus 2 nm and m and κ SLB are adjustable constants fitted to coarse grained simulation data for w s SLB . This approach gives a critical diameter for adhesion for AuNPs equal to zero.…”
Section: Resultsmentioning
confidence: 99%
“…We have used this method to calculate adhesion strengths for DMPC bilayers on planar surfaces of gold 29 , silica 30 , and titania 31 ( see table 1) as well as mixed lipid membranes with and without cholesterol for gold.…”
Section: Adhesion Strengthmentioning
confidence: 99%
“…The results of the adhesion simulations are recorded in Table 1 , data taken from previously published work for DMPC on gold 29 , silica 30 , and titania 31 .By far the greatest adhesion strength was recorded on the gold surface. For this material a reliable experimental value has been determined from chronocoulometry measurements with a gold electrode 34 .…”
Section: Adhesion Strengthmentioning
confidence: 99%